The Link between Radicalism, Human Liberation, and Ethics - Murphy, John W.; Schlaerth, Christian A. I. (Sociologija. Mintis ir veiksmas, 2010)
The point of this article is that critical philosophical reflection is vital to human liberation. This sort of philosophy reveals the fundamental (or radical) connection between human action and any resulting reality. In this way, realism is undermined, including any claims that try to diminish utopian thought. New, more humane social imagery and embodied ethics can be proposed that elevate in importance the communal character of social life.